The gutter [videorecording (DVD)] - Lester, Yassir; Moore, Shameik, 1995-; Carden, D'Arcy, 1980-; Reiser, Paul; Sarandon, Susan, 1946-; DeWitt, Keegan, 1982- (Magnolia Home Entertainment, 2025)
"When frequently fired Walt (Shameik Moore) lands a position tending bar and de-roaching shoes at his local bowling alley AlleyCatz, he feels like he's finally found a home. When money issues threaten AlleyCatz, Walt is pressured by former pro-bowler and current champion drinker Skunk (D'Arcy Carden) to accept his role as the greatest bowler ever put on this earth."--Container.